MOVEMENT COMPETENCE AND INDIVIDUAL’S GROWTH (Fiep Bulletin - online, 2012)
Physical Education in Italy is deeply changing because of the introduction of the National Indications which will replace the National Syllabus in Nursery, Primary and Secondary Schools. Each teacher is therefore induced to a disciplinary analysis in order to adopt an epistemological structure and to plan on the basis of for motor competences. A curriculum planned according to the motor competences, following the constructivist pedagogy, goes beyond the traditional didactic approach and seeks a strong interaction between the motor abilities, knowledge and the socioaffective behaviour of the person. Abilities and knowledge are instrumental to the competences to acquire even if in the field of motor education there are methodological contradictions and a lot of confusion. The documentary evaluation of the process and the results of the didactic process itself are recorded in the student's dossier which contains the activities planned and carried out, the student?s experiences and the results achieved in disciplinary and interdisciplinary field.